Global Perspectives in Ocular Oncology - Chawla, Bhavna V.; Aronow, Mary E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Eye cancers vary in presentation depending upon geographic location and access to healthcare. Global Perspectives in Ocular Oncology offers an international platform for leading ocular oncologists and multidisciplinary specialists to highlight worldwide strengths and solutions to the challenges in treating eye cancer. The goal of the book is to provide a universal view on the management of adult and pediatric tumors affecting the eye and ocular adnexa. A range of topics pertinent to the global community have been included. Organized into seven distinct sections, this book covers international collaborations and initiatives, technology and innovations, and novel treatment strategies. In addition, it provides a glimpse into the future of the specialty. The emphasis on sharing perspectives as well as the global and multidisciplinary framework of the book are unique to the market. This work will appeal to a variety of audiences including ocular oncologists and ophthalmic subspecialists, oncologists and other specialists, optometrists, geneticists, allied medical professionals, and trainees entering these disciplines.
Working Together: Specialty Interest Groups with Global Presence -- Working Together: Specialty Interest Groups with Global Presence -- Worldwide Analysis: The Global Presentation of Retinoblastoma -- International Collaborations for Characterizing Ocular Adnexal Lymphoma -- The IRIS® (Intelligent Research in Sight) Registry in Ocular Oncology -- Intravenous Chemotherapy for Retinoblastoma: A Pediatric Oncologist s Perspective -- INTRA-ARTERIAL CHEMOTHERAPY FOR RETINOBLASTOMA: A Team Effort -- Treatment Algorithms for Intraocular Retinoblastoma: An Ocular Oncologist s Perspective -- Treatment for Primary Vitreoretinal Lymphoma: The Neuro-Oncologist s View -- Treatment for Primary Vitreoretinal Lymphoma: The Neuro-Oncologist s View -- Systemic and Genetic Associations of Ocular & Ocular Adnexal Neoplasms -- A Singular View: The Ocularist s Role in Eye Loss Restoration and Rehabilitation -- Guidelines and Recommendations for Retinoblastoma Screening -- Orbital and Metastatic Retinoblastoma: Conquests and Challenges -- Metastatic Behavior of Uveal Melanoma: From Biology to Treatment -- Intra-vitreal Chemotherapy for Vitreoretinal Lymphoma -- Update on Uveal Lymphoma -- Topical Chemotherapy for Ocular Surface Squamous Neoplasia -- Surgical Management of Ocular Surface Squamous Neoplasia -- Genomics: Past, Present and Future -- Application of Deep Learning Models in the Evaluation of Histopathology of Uveal Melanoma -- Developing Prognostic Tools for Estimating Risk of Metastatic Death and Non-Metastatic Death in Individuals with Choroidal Melanoma -- Applications of Plaque Brachytherapy in Anterior Segment Ocular Tumors: A Clinical Review -- The Role of Telemedicine in Ocular Oncology -- Harnessing the Power of Artificial Intelligence -- Developing Animal Models in Ocular Oncology -- Iris Melanoma: Advanced Surgical Techniques -- The MOLES Acronym and Scoring System for Estimating Likelihood of Malignancy in Melanocytic Choroidal Tumors -- Novel Therapies for Choroidal Melanoma -- Novel Treatment Strategies for Malignant Anterior Segment Tumors -- Recent Developments in the Management of Orbital and Periocular Neoplasms -- Recent Developments in the Management of Orbital and Periocular Neoplasms -- The Rise in Immunotherapy and Associated Ocular Toxicities -- Awareness, Advocacy, and the Volunteer Sector -- Overcoming Challenges in the Delivery of Care: The Thailand Story -- Building a Retinoblastoma Service in China -- Retinoblastoma, the African Context -- The Brazilian Experience: The Retinoblastoma Awareness Campaign -- The Brazilian Experience: The Retinoblastoma Awareness Campaign -- Ocular Oncology Practice during the COVID-19 Pandemic -- Pearls from a mentor and legend in ophthalmic pathology and oncology.
Keywords: Ophthalmology; Ophthalmology; Eye Neoplasms